O estilo de vida ativo e o uso de tecnologias por universitários - Munhoz, Gabriela de Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Health studies emphasize the beneficial effects of physical activity on the lives of people who have an active lifestyle and because of this they have acquired a special importance in the universe of children and youth due to its impact in the short and long term, as a result physical activity becomes a key element for social and health policies. With the advancement of technology, studies were done to measure their influence on the lifestyle of youngsters and adults, according to the results, the time spent using them subtracts the time of participation in physical activities. However, few studies have been done verifying the time and the ways of using these technologies by them. Thus, this study aims to investigate the relationship between physical activity levels and the time and forms of use of ICT (television, computer, video games, mobile phones and others) by young people aged 18 to 25 enrolled in a Public University of Rio Claro / SP, in order to verify the relationship between these two important variables that shape the lifestyle of these students. For that, a quantitative research was carried out, based on recent studies in Spain carried out by Professor José DevísDevís. Data collection instruments were used: a self-report questionnaire, the 7D-PAR (Seven-Day Physical Activity Recall) that allowed quantifying the time allocated to physical activity in the last seven days; an adaptation of the ASAQ (Adolescent Sedentary Activity Questionnaire) questionnaire by which the time spent in the use of ICT during free time was verified; and to characterize the participants of the research, a form was filled out with the other questionnaires to fill out the participant's data (sex, age, year and course, color and work) and their socioeconomic level. The present study had a positive result on the main question raised: the use of ICT is quite large, but the participants are physically active. With this...

Estudos na área da saúde enfatizam os efeitos benéficos da atividade física na vida das pessoas que possuem um estilo de vida ativo e por conta disto os mesmos adquiriram uma importância especial no universo infantil e juvenil devido a seu impacto a curto e longo prazo, com isso a atividade física torna-se elemento chave para as políticas sociais e de saúde. Com o avanço da tecnologia, estudos foram feitos para mensurar sua influência sobre o estilo de vida de jovens e adultos segundo os resultados, o tempo gasto com o uso delas subtrai o tempo de participação em atividades físicas. Porém, poucos estudos foram realizados verificando o tempo e as formas de uso destas tecnologias por eles. Desta forma, este estudo objetiva investigar a relação entre os níveis de atividade física e o tempo e as formas de uso das TIC (televisão, computador, videogames, celular e outros) por jovens de 18 a 25 anos matriculados em uma Universidade Pública de Rio Claro/SP, a fim de verificar a relação entre estas duas variáveis importantes que configuram o estilo de vida destes estudantes. Para tal foi ealizada uma pesquisa quantitativa, baseada em estudos recentes na Espanha realizado pelo Professor José DevísDevís. Utilizou-se como instrumentos para coleta de dados: um questionário de auto-relato, o 7D-PAR (Seven-Day Atividade Física Recall) que permitiu quantificar o tempo destinado a atividade física nos últimos sete dias; uma adaptação do questionário ASAQ (Adolescent Sedentary Activity Questionnaire) pelo qual verificou-se o tempo empregado no uso das TIC durante o tempo livre; e para caracterizar os participantes da pesquisa foi entregue junto aos outros questionários uma ficha para que seja preenchido os dados do participante (sexo, idade, ano e curso, cor e trabalho) e o nível socioeconômico dos mesmos. O presente estudo obteve um resultado positivo sobre a principal questão levantada: o uso de...
Keywords: Tecnologia - Aspectos sociais; Estilo de vida; Estudantes universitarios; Qualidade de vida; Exercícios físicos; Educação fisica; Saude; Tecnologias de informação e comunicação; Rio Claro (SP)